Nationalism, governance and policymaking in Scotland: The Scottish national party (SNP) in power - Arnott, M; Ozga, J (2010)
This article explores policy development under the Scottish National Party (SNP) government, focusing on education policy. As a minority government the SNP needs to govern on the basis of co-operation and consensus. It has presented itself as a party with capacity for government but limited by the restricted autonomy of devolution. The ability to pass large amounts of legislation is more challenging for a minority government. Building new relationships with partners has been a key part of the SNP's approach to governing. This marks a shift in governing style in Scotland highlighting the importance of 'discourse' where texts (including speech) are used to promote policy aims and agendas. © 2010 The Authors.